Electrochemically grown vertically aligned ZnO nanorod array/p+-Si (100) heterojunction contact diodes - Rodriguez-Moreno, Jorge; Navarrete-Astorga, Elena; Romero, Rocío; Martín-Jiménez, Francisco de Paula; Schrebler, Ricardo; Ramos-Barrado, José R. (Elsevier, 2013)
ZnO nanorod array/p+-Si vertical heterojunction diodes, in which the ZnO nanorods have been grown by electrodeposition onto a SnO2:F thin film/glass substrate, have been fabricated by the direct-bonding technique. The heterojunction diode device showed a very good rectifying behavior with a rectification ratio of the forward-to-reverse bias current as ca. 2.5 × 104 at a voltage of ± 10 V. The current–voltage (I–V) characteristic was examined in the framework of the thermionic emission model. The obtained ideality factor and the barrier height values of the diode are 2.8 and 0.85 eV, respectively. The conduction mechanisms have been investigated from I–V characteristics as well.
Keywords: Diados; Electrodeposition; ZnO nanorod arrays; p-Type silicon; Heterojunction diode